Religion Against Violence: Insights of Contemporary Philosophy and Eastern Patristics - Olga Vasilievna Chistyakova (Religions)
This article examines the concepts of violence and religion as social phenomena of modernity. Religion and the church are presented not as specific organizations or denominations, but as important social institutions and are reflected in philosophical and anthropological terms. I carry out the idea that religion as a modern social institute in cooperation with other social communities can resist violence, especially its aggressive forms. Based on some philosophical theories, the causes of the emergence of the different forms of social violence, as well as definitions of violence, are explored. In this context, the article presents the ideas of Hanna Arendt, Carl von Clausewitz, Bertrand de Jouvenel, James Mill, and Max Weber. Special attention is paid to the conception of the mimetic origin of aggression and violence in “primitive” or “archaic religions” elaborated by the French philosopher René Girard. He compares the social roots of aggression and violence in these religions with the Biblical ones and prefers the latter for their potential in preventing and overcoming the imitation types of violence. Girard’s anthropological justification of the mentioned historical religious traditions is presented. A significant part of the paper is devoted to the views of the Eastern Church Fathers of Early Christianity, considered in the concurrence of their humanistic ideas with those of noted contemporary philosophers. I see meaningful ideas for preventing extreme forms of violence and aggression in the contemporary world in the doctrines of the Early Eastern and Byzantine Fathers, especially those of the classical patristic period. In this regard, this article presents the anthropological and humanistic teachings of Athanasius the Great, Gregory of Nazianzus, Maximus the Confessor, and John of Damascus. The Early Church Fathers’ ideas are analyzed from a philosophical point of view, as having rational and anthropological grounds which are relevant for the present day’s human existence.